Descriptive study of family caregivers’ home modifications for elder care and its Universal Design alignment - Mercado, Lliani Kichi O.
In the Philippines, elder care is primarily provided at home. As the older adult population grows, Filipino family caregivers increasingly modify residential spaces to accommodate aging family members. However, rarely are these changes analyzed using a Universal Design framework. This qualitative descriptive study investigates how selected Filipino family caregivers in Cavite modify their residential spaces to support elder care and how these modifications align with the five key principles of Universal Design, namely, equitable use, easy and intuitive, tolerance for error, low physical effort, and size and space. Using purposive sampling, five family caregivers who met the inclusion criteria were selected. Data were collected through a pre-interview questionnaire, participant-led photo documentation, and a semi-structured online interview. Thematic analysis was used to identify themes and patterns. Findings show that the most commonly used and modified areas for elder care include bedrooms, toilets, and baths. Home modifications implemented range from minor rearrangements, such as the addition of furniture and repositioning of existing room furnishings, to full structural renovations, such as building new spaces—all intended to improve comfort, safety, accessibility, and caregiving efficiency. Although caregivers had no formal design training, most modifications reflected an intuitive application of Universal Design principles. This study highlights how cultural values, caregiving roles, and real-life constraints shape decisions on the use of space and how user-informed modifications can guide more inclusive, sustainable residential design for aging populations.